Middle Ear Ventilation Tube in Patients with Cleft Palate at King Abdulaziz University Hospital - Talal A. AlKhatib,; Yasir S. Jamal,; Abdulaziz H. Alghamdi,; Bhaa M. Simbawa,; Yahya H. Ghunaim,; Lujain A. Bukhari, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This study aims to determine the number of patients with cleft palate requiring treatment for otitis media with effusion. Speech and hearing assessments were also considered. We conducted a retrospective study from January, 2005 through December, 2012 at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, on otitis media with effusion in patients with cleft palate. We reviewed patients’ medical records to determine the number requiring treatment for otitis media with effusion, the timing of middle ear ventilation tube insertion, the number of tubes to be inserted, and the type of tube to be used. Data were collected from the patients’ medical records. Ethical approval was obtained by the university’s ethical committee. A total of 101 patients were diagnosed with cleft palate spectrum. Among them, we found that only 12 patients had a hearing assessment and tympanograms performed followed by middle ear ventilation tube insertion. This may indicate the need for more involvement of the otolaryngologists in the multidisciplinary clinical teams for evaluating cleft palate patients.